Factors That Cause Delay of Surgical Treatment in Strabismus - Turkcuoglu, Peykan; Aydemir, Orhan; Kaya, Murat; Turgut, Burak (Turkish Ophthalmological Soc, 2008)
Purpose: To determine the factors that delayed the diagnosis and surgical intervention in patients who underwent strabismus surgery. Method: Between January-December 2006 patients who underwent strabismus surgery or their parents were given a questionnaire about the causes of delay of diagnosis or surgical intervention. Results: The ages of 38 male and 39 female patients ranged between 9 months and 60 years. 45 patients were under the age of 10 (strabismus was recognized under the age of 6 months in 18; above the age of 6 months in 27 of them). The duration from the first recognition to admition to a doctor was ranged between 1 month and 43 year (86 +/- 108), 1 and 60 months (11 +/- 17), 1 and 42 months (6 +/- 11) in groups above age of ten years, under the age of 6 months, above the age of 6 months, respectively. 17 (94%), 21 (78%) and 29 (91%) patients first admitted to an ophthalmologist in the group above age 10 years, in the group under age 6 months and in the group above age 6 months, respectively. In two of the seventy-seven patients diagnosis of strabismus was delayed because of ophthalmologists. The mean time periods that the patients accepted the surgical intervention were 6 +/- 12 months in the group under the age 6 months; 3 +/- 10 months in the group above the age 6 months; 25 +/- 48 months in the group above ten years of age. % 62 of the patients accepted the surgical intervention promptly, however % 38 of the patients rejected surgery due to affair of being worser, fear of unknown cause, distrust to the doctor, anesthesia risks, inattention, familial problems and belief to improve spontaneously. Conclusion: More attention must be given to the education of the ophthalmologists and public in order not to lose important time in strabismus surgery.
Keywords: Strabismus; surgical intervention; delay